2004
DOI: 10.1136/adc.2003.032078
|View full text |Cite
|
Sign up to set email alerts
|

Household and family characteristics of street children in Aracaju, Brazil

Abstract: Aims: To describe the family background of street children in Aracaju, Brazil, their parents' perception of street life, and the reasons for the high prevalence of males observed among street children. Methods: Cross sectional study using semi-structured interviews and qualitative focus group discussions with parents of purposively selected index street children. Results: Fifty eight families were enrolled. Most participants were single parent, female headed families living in slums or low cost housing, with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 12 publications
5
45
0
7
Order By: Relevance
“…5 Some data have shown that Brazilian children on the streets often come from a single-mother-headed family and that poverty, victimization, and a troubled family background are factors associated with working on the streets. 6,7 Consistent with this finding, international data have shown a similar pattern in other countries. In a 1993 UNICEF survey of 1,000 Ethiopian street children, only 23% of these children lived with both parents at home.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…5 Some data have shown that Brazilian children on the streets often come from a single-mother-headed family and that poverty, victimization, and a troubled family background are factors associated with working on the streets. 6,7 Consistent with this finding, international data have shown a similar pattern in other countries. In a 1993 UNICEF survey of 1,000 Ethiopian street children, only 23% of these children lived with both parents at home.…”
Section: Introductionsupporting
confidence: 77%
“…In addition, adolescents older than 14 do not appeal to passersby as much as younger children do. 2,6,11,28 The children on the streets in this sample had more years of education compared to their siblings; however, they also had more grade repetition, although the difference was only barely significant. In Brazil, the public school system does not retain students due to their grades, but rather due to school absences, and children have to stay in school for only one period of the day (either from early morning to noon or the entire afternoon).…”
Section: Discussionmentioning
confidence: 87%
“…5 Qualitative studies in Brazil suggest that family breakdown combined with economic problems, peer pressure, and drug use are driving factors towards street life; these studies provide alarming insights into the risks these children face. 6,7 Reports in Peru are similar; a survey of 134 street children in Lima found that 81% admitted alcohol consumption and 92% admitted to using 'terokal', a volatile solvent. 8 These children often survive by working in the informal sector.…”
Section: Introductionmentioning
confidence: 94%
“…[4][5][6][7] A study in La Paz, Bolivia, reported that up to 85% were victims of physical abuse, with children also reporting experience of sexual abuse (20%), serious medical conditions (53%), use of alcohol (58%), and inhalation of volatile solvents (88%). 5 Qualitative studies in Brazil suggest that family breakdown combined with economic problems, peer pressure, and drug use are driving factors towards street life; these studies provide alarming insights into the risks these children face.…”
Section: Introductionmentioning
confidence: 99%
“…Por fim, diversos outros fatores explicavam parcialmente a presença de jovens nas ruas. Alguns estudos apontaram a pobreza como o fator de maior importância etiológica, juntamente com o tamanho das famílias e a grande proporção dessas famílias chefiadas por mulheres (Abdelgalil, Gurgel, Theobald, & Cuevas, 2004;Barros & Mendonça, 1996;Juárez, 1996;Lusk, 1992;Paludo & Koller, 2008;Rizzini & Lusk, 1995;Rosa et al, 1992).…”
Section: O Estudo Da Socialização De Jovens Na Rua E O Método Etnográunclassified